Evaluación del sistema de protección contrafuegos y seguridad y prevención de riesgos de incendio en el Campus San Felipe de la UTC. Propuesta del plan de emergencias y contingencias del Campus. - Pérez Hidalgo, Richard Francoy (2011)
Any productive activity is exempt of risks, beyond the commonly evaluated, analyzed and considered in every job, there are those that relate to the infrastructure of the job itself, and can cause serious damage or affect persons who work daily in a labor activity. Inside these risks include those considered locatives that may occur such as fires, among others, major accidents or those produced by the very nature such as flooding, eruptions, earthquakes, and others. From this point of view is too important that the constructions continue existing safety regulations, such as: the installation of smoke detectors or automatic water sprinklers, as well as equipped fire hydrants located at strategic locations. But the security goes beyond the automatic and manual devices; there must be continuous training for staff who works in these buildings, as well as the appropriate technical information to users. But what to do if the buildings are already built and staff do not know how to act in case of raise an incident or event adverse, then comes the importance of having a Plan for emergencies and contingencies, that is a technically elaborate instrument which identifies, analyzes, evaluates, and aims to decrease or control of such risks and program the most suitable measures that should be taken both in infrastructure and people with the purpose of preserving the life of people and material goods of an institution. There are several methods that can be used for the assessment of such risks, will seek to do so which is best suited to the reality of the institution or company, as well as greater experience has the technical implementation. With regard to the format of the plan must conform to existing regulations in each country in strict form, in the Ecuador this policy is dictated by the firemen.